180 - OCCUPATIONAL RISKS IN INTENSIVE CARE UNIT: LITERATURE REVIEW (Fiep Bulletin - online, 2011)
In the ICU are primordial resources that provide safety for patients and staff under normal and emergency conditions, so studies with the objective knowledge of occupational hazards and use of personal protective equipment among these workers are present. Thus, the objective of this study is to identify the characteristics of scientific studies on occupational hazards in the ICU in the databases of VHL / Center and the Medical Journal (PUBMED), for the year, country, type and availability of publication, language, type study and approach, topic category. This is a literature review, held electronically, in August/2009 That way, he met a total of 22 papers including 18 in LILACS, BDENF 2 in and 2 in PUBMED. Of these, the majority of studies published in 2004 (18.1%),in Brazil (77.2%), a scientific article (68.2%), available in summary form (72.7%), Portuguese (77 , 3%), using descriptive studies (81.8%) and qualitative (72.7%). In the themes highlighted in the nursing staff (54.5%), the types of risks (22.7%) and health education (13.6%). In study we focus on the importance of continuing education for staff regarding precautionary measures against biological agents, physical and chemical reformulation of policies for the prevention of occupational risks, ongoing assessment of health workers, hospital and development of risk map are part of an intervention strategy for reducing occupational risks in the ICU.
Keywords: occupational risk; intensive care uniy; nursing; publications